Give them a break! Did activation of young welfare recipients overshoot in Germany? (A regression discontinuity analysis) - Joachim Wolff; Anton Nivorozhkin (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
In Germany, due to special rules 15- to 24-year-old welfare recipients, registered with Public Employment Office, are highly targeted by mandatory activation policies. This paper investigates the effects of the special rules in terms of enhancing the (re-)employment probability, increasing earnings and reducing benefit dependency of targeted people in East and West Germany in the short- and the long-run. Using registry dataset of the inflow into unemployment and welfare over the period October 2005 to January 2006 the paper exploits the age related eligibility rule to identify a suitable counterfactual using a regression discontinuity design. Our estimates imply zero or negative effects of targeting for selected population subgroups. A possible explanation to our finding is that an excessive targeting of young welfare recipients by active labour market programmes may lead to a low quality matches between programmes and participants.
Keywords: C13; I38; J68; 330